The Communication Skills Profile of Pre-Service Biology Teachers - Astuti Muh. Amin; Fitriyah Karmila; Yuni Pantiwati; Romi Adiansyah; Ahmad Yani (Jurnal Penelitian Pendidikan IPA, 2022)
The focus of learning design and learning innovations for the twenty-first century is preparing students with communication skills. Students must have communication skills to effectively transfer scientific knowledge, processes, knowledge, insights, and other important data. This study aimed to determine the profile of communication skills possessed by pre-service biology teachers at IAIN Ternate. This is a quantitative descriptive study involving 65 students from the Tadris Biology Department at IAIN Ternate. The research was conducted during the even semester of the 2021/2022 academic year. Observation sheets of verbal and nonverbal communication were used to collect data. The technique for collecting data is direct observation (experience) of the learning process and interactive class discussion in the target classroom. The results indicated that pre-service biology teachers' verbal and nonverbal communication abilities were extremely deficient. These findings provide educators with an overview of effective learning approaches for training students to be independent and proficient in 21st-century skills